Designing an ultra‐short antibacterial peptide with potent activity against Mupirocin‐resistant MRSA. (12th September 2018) - Arfan, Giovinna; Ong, Chu Yang Fann; Ng, Siew Mei Samantha; Lau, Qiu Ying; Ng, Fui Mee; Ong, Esther Hong Qian; Hill, Jeffrey; Chia, Cheng San Brian
Abstract: Staphylococcus aureus is the pathogen responsible for the majority of human skin infections. In particular, the methicillin‐resistant variety, MRSA, has become a global clinical concern. The extensive use of mupirocin, the first‐line topical antibacterial drug of choice, has led to the emergence of mupirocin‐resistant MRSA globally, resulting in the urgent need for a replacement. Antimicrobial peptides are deemed plausible candidates. Herein, we describe a structure–activity relationship approach in the design of an ultra‐short peptide with potent anti‐MRSA activity with a rapid, bactericidal mode of action. Coupled to a low cytotoxic activity, we believe our lead compound can be developed into a topical antibacterial agent to replace mupirocin as the first‐line drug for treating MRSA skin infections. Abstract : A recently reported synthetic nonapeptide, P9‐4, showed promise as a topical antibacterial drug candidate for treating bacterial skin infections. A structure–activity relationship study was conducted to optimize its antibacterial activity against the notorious skin pathogen, Staphylococcus aureus . This resulted in a novel doubly charged nonapeptide with improved antibacterial activity that can be further developed as a topical antibacterial drug candidate.